DETERMINATION OF THE EFFECT OF SOLVENT COMBINATION IN THE GLUCOMANNAN PURIFICATION PROCESS FROM PORANG FLOUR - Audreena, Qisthyadevany
Glucomannan is a hydrocolloid that functions as a thickener, emulsifier and stabilizer in various industries. All of the glucomannan used by the Indonesian food industry is imported and Indonesia is the second largest importer of glucomannan in the world for the last 10 years (2012-2022). Glucomannan can be obtained from local porang tubers (Amorphophallus muelleri Blume) which are usually processed into chips or flour. Porang flour that went through a purification process with ethanol solvent can produce glucomannan flour that complies with commercial standards. Isopropyl alcohol (IPA) has the potential to replace ethanol as solvent so that the glucomannan purification process becomes more economical. In addition, the use of potassium hydroxide (KOH) in the glucomannan purification process can contribute to extracting more impurities. This study aims to determine the effect of the combination of 70% IPA, 70% ethanol, 2.5 m KOH solution on the quality of glucomannan and determine the effect of adding porang glucomannan on the quality of jelly. This research consisted of 2 stages, namely purification of glucomannan using IPA, ethanol, and KOH solvents and production of jelly using porang glucomannan. The experimental design of this research is a simplex centroid mixture design using mass fractions. Characterization of the quality of porang glucomannan was carried out on yield, viscosity, yield, and whiteness index, while the characterization of jelly quality was carried out on gel strength. The results of this study indicate that the combination of 70% IPA, 70% ethanol, 2.5 m KOH solution in the purification process of porang glucomannan from porang flour has a significant effect on the whiteness index of porang glucomannan, but has no significant effect on the yield, viscosity, and purity of porang glucomannan . The best glucomannan flour within the variation range of this study was obtained with a combination of 70% IPA:70% ethanol (1:1) solvent which had a yield value of 94.40%, viscosity of 20.902 cP, glucomannan purity of 63.40% (based on soluble dietary fiber) , and whiteness index 75.29. This study also found that the addition of porang glucomannan had no significant effect on the gel strength of jelly.